Relationship between non-alcoholic fatty liver disease during pregnancy and abnormal glucose metabolism during and after pregnancy. (17th December 2019) - Sattari, Maryam; Bril, Fernando; Egerman, Robert; Kalavalapalli, Srilaxmi; Cusi, Kenneth
Abstract : While non-alcoholic fatty liver disease (NAFLD) is associated with increased risk of impaired glucose tolerance and type 2 diabetes mellitus (DM) in non-pregnant patients, the clinical significance of NAFLD during pregnancy is still unclear. We hypothesized that sonographic findings of NAFLD during pregnancy would be associated with gestational diabetes mellitus (GDM) and predict abnormal postpartum glucose metabolism. NAFLD was assessed by ultrasound during and after pregnancy. Standard 2-hour 75 g oral glucose tolerance test (OGTT) was used during pregnancy and post partum to establish GDM and the diagnosis of normal, impaired fasting glucose, or DM. We also measured plasma insulin, C peptide, and free fatty acids (FFA) concentration during an OGTT to evaluate glucose tolerance, insulin secretion and insulin resistance. Of the 84 subjects, 12 had sonographic evidence of NAFLD (5 of whom had OGTT post partum). There was a non-significant trend toward higher mean weight and body mass index during and after gestation in the NAFLD group, but no statistically significant differences in mean age, ethnicity, prepregnancy and postpregnancy hemoglobin A1C values, and postpartum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), glucose, insulin, or FFA. We did not find an association between sonographic evidence of NAFLD during the third trimester of pregnancy and abnormal glucose metabolism during or after pregnancy. This study also suggests that while AST and ALT are not reliable diagnostic tools for NAFLD during the postpartum period, ultrasound is a reasonably safe, practical, and cost-effective modality to assess maternal hepatic fat during pregnancy.